2019
DOI: 10.1155/2019/1832025
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Attenuates LPS-Induced Cardiac Dysfunction by Inhibition of Mitochondrial Function via the ER Pathway

Abstract: Sepsis is a life-threatening organ dysfunction syndrome with a high rate of mortality. It is caused by an abnormal immune response to infection, and the occurrence of sepsis-induced cardiomyopathy is the primary cause of death. The present study was designed to examine the effects of adenosine on lipopolysaccharide- (LPS-) induced cardiac anomalies and the underlying mechanisms involved. Adenosine (25, 50, and 100 mg/kg, i.g., 2 times/day) was administered for three days, followed by the induction of sepsis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…MAPK-p38 and NF-κB are important signaling pathways associated with myocardial cell injury ( 6 ). In the present study, to further verify the function of DUSP1, a cell model using H9C2 cells in which DUSP1 was downregulated was constructed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK-p38 and NF-κB are important signaling pathways associated with myocardial cell injury ( 6 ). In the present study, to further verify the function of DUSP1, a cell model using H9C2 cells in which DUSP1 was downregulated was constructed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pathological manifestations of sepsis-induced cardiomyopathy (SIc) are as follows: Spot hemorrhage on the myocardial surface, extensive myocardial hemorrhage, inflammatory cell infiltration, interstitial edema and degeneration and necrosis of some myocardial cells (2)(3)(4). during the process of sepsis, bacterial infection activates Toll-like receptor (TLR) via pathogen-related molecular patterns, such as lipopolysaccharide (LPS), thereby inducing MAPK and NF-κB pathway activation, which promotes the infiltration of inflammatory cells into myocardial tissue and triggers myocardial inhibition (5)(6)(7)(8)(9). Therefore, it is currently hypothesized that the inhibition of the NF-κB and MAPK pathways can effectively reduce the inflammatory response of the septic myocardium and is one of the strategies used to improve SIc.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial dysfunction in sepsis has multiple complex manifestations, including Original Article decreased ejection fraction and myocardial contractility. Additionally, previous studies have shown that the presence of acute cardiac dysfunction in sepsis is an indicator of poor prognosis (6,7).…”
Section: Introductionmentioning
confidence: 98%
“…In echocardiography, EF and FS are widely used as alternative markers of cardiac contractility and cardiac function. Zeng et al reported that high doses of adenosine could significantly improve LVEF and LVFS in LPSinduced septic rats(6). In this study, we first assessed the index effect of LVEF and LVFS in LPS-induced rats by echocardiography.…”
mentioning
confidence: 97%
“…Septic myocardial dysfunction has complex manifestations, including reduced ejection fraction and myocardial contractility (5). Additionally, acute cardiac insufficiency is an indicator of poor prognosis in patients with sepsis (6,7).…”
Section: Introductionmentioning
confidence: 99%